2009
DOI: 10.1002/cbf.1580
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the lactate threshold and maximal blood lactate steady state intensity in aged rats

Abstract: The reliability of the lactate threshold (LT) determined in aged rats and its validity to identify an exercise intensity corresponding to the maximal blood lactate steady state (MLSS) were analyzed. Eighteen male aged Wistar rats (approximately 365 days) were submitted to two incremental swimming tests until exhaustion, consisting of an initial load corresponding to 1% of body mass (BM) and increments of 1% BM at each 3-min with blood lactate ([lac]) measurements. The LT was determined by visual inspection (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 46 publications
8
40
0
3
Order By: Relevance
“…The training intensities used in the present study were probably higher compared to the work of Le Page and Rossi. In fact, in the present study EAE-TR H and CON-TR H exercise intensity is probably near the anaerobic threshold [17,18]. Therefore, the present findings and the above-described work of others suggest that exercise intensity determines the impact of training on the course of EAE and that the optimal endurance training intensity in EAE is probably near the anaerobic threshold.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The training intensities used in the present study were probably higher compared to the work of Le Page and Rossi. In fact, in the present study EAE-TR H and CON-TR H exercise intensity is probably near the anaerobic threshold [17,18]. Therefore, the present findings and the above-described work of others suggest that exercise intensity determines the impact of training on the course of EAE and that the optimal endurance training intensity in EAE is probably near the anaerobic threshold.…”
Section: Discussionsupporting
confidence: 73%
“…TR M and TR H rats ran 1 hour at respectively 11m/min (15° inclination) and 18m/min (25° inclination). Although not measured, running intensity for TR H rats was probably just below the anaerobic threshold [17,18]. Animals were encouraged to walk/run by means of low intensity electrical shocks.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the type of the exercise (treadmill versus FRW) as well as the protocol may influence LT. In Wistar rat, LT identified by an INCP test is usually similar to its MLSS 23 . This is contradictory to results observed in our study.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we suggested that the muscarinic antagonist atropine inhibits the excitatory parasympathetic pathway, fosters gastric relaxation, and increases gastric retention in exercised rats (13). Acute exercise promotes the release of several vasodilator agents such as nitric oxide, prostaglandins, and the endothelial-derived hyperpolarizing factor (32,33).…”
Section: Discussionmentioning
confidence: 82%
“…High-intensity exercise raises blood levels of NO and VIP (11), but also promotes the release of corticosterone (12). Additionally, atropine has been shown to delay GE (13). We hypothesized that the acute exercise-induced delay in GE involves vagal nerves that are associated with the corticotropin-releasing factor (CRF) and VIP, as well as cGMP-NO/VIP pathways.…”
Section: Introductionmentioning
confidence: 99%